RESPECT FOR THE WILL OF THE ELDERLY ILL PERSONS - MARIA, Ingrid (MEDECINE LEGALE DROIT MEDICAL, 2025)
While the primacy given to respect for the will is undeniable today in medical matters, it is important to know whether this injunction is not illusory when this will comes from elderly ill persons. French law distinguishes, among these people, those who are able to express their will from those who are not. Respect for the will of the first ones is essential even if these people are placed in a position of legal protection. For the second, it is necessary to refer to previous manifestations of will (advance directives) and / or to testimonies of relatives (support person or others). These rules are largely unknown by most medical members. The protection mechanisms for the most fragile are, moreover, not accessible. The promotion of autonomy could therefore only remain a beautiful mantra.